Implementation of Ergonomic Criteria for Evaluating the Logistic Mobile App User Interface Design - Alexandra, Hany; Amri, Muhammad Ulil; Putri, Fadhilah Eka; Paramita, Andi Jamiati; Nainggolan, Rena; Tobing, Fenina Adline Twince (Universitas Multimedia Nusantara, 2025)
The rapid growth of digital logistics has increased dependence on mobile delivery applications to manage shipments, package information, and courier operations under strict time constraints. Nowdays, ergonomic and usable user interface design is essential to reduce cognitive load, minimize errors, and maintain operational efficiency. However, empirical usability research focusing specifically on delivery service applications remains limited, particularly studies conducted in realistic usage contexts. This study evaluates the ergonomic quality of a mobile delivery application using online usability testing. A quantitative evaluation framework is applied, employing three established metrics: the System Usability Scale (SUS), task completion time, and error rate. These measures capture perceived usability, interaction efficiency, and error occurrence during representative delivery-related tasks. The findings reveal key usability issues related to navigation structure, information presentation, and interaction flow that negatively affect user performance. The result, study proposes data-driven UI design improvements aimed at enhancing clarity, efficiency, and cognitive ergonomics. The novelty is its integration of online usability testing with ergonomic evaluation in the delivery application domain, an area that remains underrepresented in recent human–computer interaction research. The outcomes provide scalable evaluation benchmarks and practical design guidance to support the development of more efficient, user-friendly, and ergonomically appropriate mobile delivery applications.